The relationship between entrepreneurial passion, entrepreneurial self efficacy, and entrepreneurial intention in housewives context - Devani Laksmi Indyastuti; Lusi Suwandari; Krisnhoe Rachmi Fitrijati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
This study examined the relationship between entrepreneurial passion, entrepreneurial self-efficacy, and entrepreneurial intention. This hypothesis proposes that entrepreneurial passion positively affects entrepreneurial intention. Furthermore, this study also hypothesizes that entrepreneurial emphasizing on entrepreneurial intention is mediated by entrepreneur self-efficacy. The present study takes a sample from housewives who run businesses in Banyumas. This study uses a convenience method for choosing 236 housewives who run businesses. This method is chosen because there is no sampling frame in this population. The results show that Entrepreneurial passion positively influences entrepreneurial intention. Entrepreneurial self-efficacy mediates the relationship between entrepreneurial passion and entrepreneurial intention.